Negative electrode material, preparation method thereof and secondary battery
By constructing a solid solution phase structure of lithium metal and metal alloy in the lithium metal negative electrode, the problem of dendrites of lithium metal negative electrode is solved, high lithium utilization rate and cycle stability are achieved, and the energy density and safety of the secondary battery are improved.
Patent Information
- Application Number
- CN202411867370.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The lithium metal negative electrode is prone to form dendrites during the battery cycle, reducing the Coulomb efficiency and cycle life of the battery, and posing safety risks. The prior art sacrifices the mass fraction and utilization rate of lithium metal while optimizing the cycle life.
By constructing a solid solution phase structure formed by lithium metal and metal alloy, a solid solution phase is formed with a metal alloy with a valence electron concentration of less than 6.87, it promotes rapid transportation of lithium atoms inside the negative electrode and bulk phase deposition, and reduces the occurrence of dendrites.
The high utilization rate and mass fraction of lithium metal are achieved, which significantly improves the cycle stability and safety of the negative electrode material, and improves the energy density and Coulomb efficiency of the secondary battery.
Smart Images

Figure CN119890252A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of secondary batteries, and in particular to a negative electrode material and a preparation method thereof, and a secondary battery. Background Art
[0002] Lithium metal has a high theoretical specific capacity (3860 mAh g - ¹) and a lower redox potential (-3.04 V) than the standard hydrogen electrode, and is therefore considered to be the preferred negative electrode material for high energy density power sources. However, the dendrite growth problem faced by lithium metal negative electrodes during battery cycling has become a major obstacle to their widespread application. The uncontrolled growth of dendrites will not only reduce the Coulombic efficiency (CE) and cycle life of the battery, but may also induce internal short circuits, posing a major safety hazard.
[0003] At present, some results have been achieved in inhibiting the growth of dendrites of lithium metal anodes by optimizing electrolytes and additives, designing artificial protective layers, and adopting three-dimensional host structures in the anode. However, the current lithium metal anode design sacrifices the mass fraction and lithium utilization of lithium metal while pursuing a good cycle life, resulting in the actual capacity being far lower than the theoretical value of lithium metal, thus failing to give full play to its high specific capacity advantage.
[0004] Therefore, how to optimize the negative electrode structure, achieve high lithium utilization and mass fraction, and effectively control the deposition and stripping behavior of lithium without sacrificing the battery cycle life, so as to improve the energy density and cycle stability of lithium metal batteries, has become a key issue that needs to be urgently solved in the current research and development of high energy density power sources. Summary of the invention
[0005] In view of this, the main purpose of the present disclosure is to provide a negative electrode material and a preparation method thereof and a secondary battery, in order to at least partially solve at least one of the above-mentioned technical problems.
[0006] To achieve the above purpose, the technical solution of the present invention is as follows:
[0007] In one aspect of the present disclosure, there is provided a negative electrode material, comprising:
[0008] Lithium metal and metal alloys, wherein
[0009] The metal alloy includes a metal that forms a solid solution with lithium metal;
[0010] The mass fraction of lithium metal ranges from 60% to 90%;
[0011] The valence electron concentration of metal alloys is less than 6.87;
[0012] The utilization rate of lithium metal in the negative electrode material is higher than 35%.
[0013] In another aspect of the present disclosure, a method for preparing the above-mentioned negative electrode material is provided, comprising:
[0014] Under the protection of an inert gas, the lithium metal and the metal alloy are melted and mixed to form a molten alloy mixture;
[0015] After cooling the molten alloy mixture, a negative electrode material is obtained.
[0016] In another aspect of the present disclosure, a secondary battery is provided, comprising a negative electrode, a positive electrode, an electrolyte and a separator, wherein:
[0017] The negative electrode includes the negative electrode material mentioned above, the separator is located between the negative electrode and the positive electrode, and the electrolyte is filled in the gaps between the separator and the positive electrode and the negative electrode.
[0018] According to an embodiment of the present disclosure, a negative electrode material is provided, including lithium metal and a metal alloy. A metal alloy having a valence electron concentration of less than 6.87 is used to form a solid solution phase structure with lithium metal. The solid solution phase structure can significantly increase the diffusion rate of lithium atoms in the metal alloy phase, thereby promoting the rapid transport of lithium atoms inside the negative electrode and realizing the bulk deposition of lithium metal. The occurrence of side reactions such as lithium dendrites on the negative electrode material is effectively reduced, thereby improving the cycle stability and safety of the battery. In addition, by regulating the mass fraction of lithium metal in the negative electrode material (60%~90%), it is ensured that the negative electrode material has a high lithium metal utilization rate (higher than 35%) and a high mass specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A high-resolution transmission electron microscope image of the negative electrode material in Example 1 of the present disclosure and a corresponding energy dispersion X-ray spectrum surface distribution image;
[0020] Figure 2 is a voltage-specific capacity curve of the negative electrode material in Example 1 of the present disclosure during the charge and discharge process;
[0021] Figure 3 is a diffusion coefficient diagram of lithium ions in the negative electrode material in Example 1 of the present disclosure;
[0022] Figure 4 A comparison chart of the coulombic efficiency of a half-cell assembled with the negative electrode material and copper metal foil in Example 1 of the present disclosure and a half-cell assembled with the negative electrode material and copper metal foil in Comparative Example 1;
[0023] Figure 5 The figure is a comparison of the cycle performance of the secondary batteries respectively assembled with the negative electrode materials in Example 1 and Comparative Example 1;
[0024] Figure 64 is a comparison chart of the mass specific capacity of the negative electrode materials in Examples 1 to 5 of the present disclosure. DETAILED DESCRIPTION
[0025] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.
[0026] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.
[0027] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0028] In the process of exploring high energy density battery technology, especially for secondary batteries, lithium metal has been widely used due to its superior theoretical specific capacity (3860 mAh g -1 ) and a low redox potential (-3.04 V) make it an ideal choice for negative electrode materials. However, lithium metal is prone to form dendrites during the battery charge and discharge cycle, which not only reduces the battery's Coulombic efficiency and shortens the battery's cycle life, but may also cause internal short circuits in the battery, increasing safety risks. Although the current optimization of the lithium metal negative electrode design can ensure the cycle stability of the battery, it usually sacrifices the mass fraction of lithium metal in the lithium metal electrode and the lithium metal utilization rate, resulting in the actual specific capacity of the negative electrode being far lower than the theoretical value, and failing to fully tap the high specific capacity potential of lithium metal.
[0029] In the process of realizing the concept of the present disclosure, it was found that by constructing a solid solution phase structure formed by lithium metal and metal alloy, due to the certain solid solubility between the metal alloy and lithium, a rapid diffusion path is provided for lithium atoms to promote the uniform diffusion of lithium atoms in the solid solution phase, and realize the bulk deposition of lithium atoms, thereby effectively inhibiting the occurrence of side reactions such as lithium dendrites. The prepared negative electrode material not only performs well in terms of cycle life and safety, but also has a high lithium metal utilization rate (higher than 35%) and lithium metal mass fraction (60%~90%), which significantly improves the mass specific capacity of the negative electrode material. The secondary battery assembled by combining the above-mentioned negative electrode material with the positive electrode material can significantly improve the energy density of the secondary battery, providing a new direction for the development of the next generation of high energy density battery technology.
[0030] According to an embodiment of one aspect of the present disclosure, a negative electrode material is provided, the negative electrode material comprising:
[0031] Lithium metal and metal alloys, wherein
[0032] The metal alloy includes a metal that forms a solid solution with lithium metal;
[0033] The mass fraction of lithium metal ranges from 60% to 90%;
[0034] The valence electron concentration of metal alloys is less than 6.87;
[0035] The utilization rate of lithium metal in the negative electrode material is higher than 35%.
[0036] For example, the mass fraction of lithium metal may be, for example, 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc. The valence electron concentration of the metal alloy may be, for example, 6.86, 6.70, 6.55, 6.00, 5.50, etc. The utilization rate of lithium metal in the negative electrode material may be, for example, 35%, 40%, 50%, 60%, 70%, 80%, 85%, 90%, etc.
[0037] According to an embodiment of the present disclosure, a solid solution phase structure is constructed by a metal alloy having a valence electron concentration of less than 6.87 and lithium metal. In the solid solution phase, there is a certain solid solubility between the metal alloy and lithium metal, so that the chemical potential inside the bulk phase changes continuously, and there is a continuous driving force for the diffusion of lithium atoms, thereby driving the rapid and uniform mutual diffusion of lithium atoms in the metal alloy phase, as well as the rapid transportation inside the negative electrode, to achieve bulk deposition of lithium metal. The formation of lithium dendrites is effectively prevented, and the cycle life, safety and stability of the negative electrode material are improved. In addition, by regulating the mass fraction of lithium metal in the negative electrode material (60%~90%), it is ensured that the negative electrode material has a high lithium metal utilization rate (higher than 35%) and a high mass specific capacity.
[0038] According to an embodiment of the present disclosure, the metal capable of forming a solid solution with lithium metal is selected from at least two of indium (In), magnesium (Mg), silver (Ag), cadmium (Cd), zinc (Zn) and aluminum (Al), preferably at least four of indium, magnesium, silver, cadmium, zinc and aluminum.
[0039] According to an embodiment of the present disclosure, by selecting a metal alloy with a valence electron concentration of less than 6.87, it is ensured that the metal elements in the metal alloy and the lithium metal can maintain a body-centered cubic phase (BCC) structure during the cyclic charge and discharge process. The BCC phase enables a stable solid solution phase structure to be constructed between the metal alloy and the lithium metal, thereby significantly enhancing the structural stability of the negative electrode material, effectively promoting the diffusion efficiency of lithium atoms in the metal alloy phase, and greatly reducing the occurrence of side reactions. In addition, the synergistic effect of multiple metals can cause metal alloys to be more inclined to form a solid solution phase rather than a complex intermetallic compound, which can not only enhance the mechanical properties of the metal alloy, but also avoid the performance deterioration caused by phase separation. The multi-component alloy design also effectively disperses stress concentration, reduces lithium deposition in local areas, and further improves the overall safety of the battery.
[0040] According to an embodiment of the present disclosure, the molar ratio of lithium metal to the metal alloy is 55-90:1, for example, it can be 55:1, 60:1, 70:1, 80:1, 85:1, 87:1, 89:1, 90:1, etc.
[0041] According to the embodiments of the present disclosure, by controlling the molar ratio of lithium metal to metal alloy in the negative electrode material, the mass fraction of lithium metal in the negative electrode material is ensured to be controlled within the range of 60% to 90%, thereby improving the mass specific capacity of the negative electrode material.
[0042] According to another embodiment of the present disclosure, a method for preparing the above-mentioned negative electrode material is provided, comprising:
[0043] Under the protection of an inert gas, the lithium metal and the metal alloy are melted and mixed to form a molten alloy mixture;
[0044] After cooling the molten alloy mixture, a negative electrode material is obtained.
[0045] According to the embodiments of the present disclosure, the lithium metal and the metal alloy are uniformly mixed by heating and melting, ensuring that the two can be fully fused to form a negative electrode material with a solid solution phase structure. The solid solution phase structure is conducive to the rapid diffusion and transport of lithium atoms in the negative electrode material, achieving the bulk deposition of metallic lithium, thereby reducing the generation of battery side reactions.
[0046] According to an embodiment of the present disclosure, the time of melt mixing is 10 to 60 min, for example, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, etc.; the temperature of melt mixing is 180 to 1000°C, for example, 180°C, 350°C, 450°C, 650°C, 700°C, 1000°C, etc. During the melt mixing process, the lithium metal and the metal alloy are uniformly mixed by high-speed stirring, and the rotation speed of the high-speed stirring is 100 to 500 r / min, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, etc., and a stirring bar or a stirring paddle can be used for stirring.
[0047] According to the embodiments of the present disclosure, melt mixing of lithium metal and metal alloy at a temperature of 180-1000°C can ensure that all metals involved in the mixing can be completely melted to form a uniform molten alloy mixture, while avoiding the problem of excessive volatilization of metals due to excessively high temperatures, thereby ensuring the stability of the lithium metal and metal alloy components in the negative electrode material.
[0048] According to an embodiment of the present disclosure, cooling includes: natural cooling or liquid nitrogen cooling, preferably liquid nitrogen cooling. The cooling process is carried out under the protection of an inert gas, and the inert gas is preferably argon (Ar).
[0049] According to the embodiments of the present disclosure, the temperature of the metal can be quickly reduced by cooling with liquid nitrogen. The rapid cooling process helps to control the microstructure of the negative electrode material and eliminate the internal stress that may be generated during the melting and solidification process, thereby significantly improving the overall performance of the negative electrode material and improving its dimensional stability. In addition, cooling with liquid nitrogen can also promote the refinement of metal grains, which not only enhances the hardness and strength of the negative electrode material, but also reduces the grain size of the material, further improving the mechanical properties of the negative electrode material.
[0050] According to another embodiment of the present disclosure, a secondary battery is proposed, comprising a negative electrode, a positive electrode, an electrolyte and a separator, wherein the negative electrode comprises the above-mentioned negative electrode material, the separator is located between the negative electrode and the positive electrode, and the electrolyte is filled in the gap between the separator and the positive electrode and the negative electrode.
[0051] According to the embodiments of the present disclosure, by controlling the mass fraction of lithium metal in the negative electrode material within the range of 60% to 90%, the utilization rate of lithium metal in the negative electrode material is ensured to be higher than 35%. The prepared negative electrode material is used to replace the pure lithium metal negative electrode material, and the deposition and stripping behavior of lithium metal are effectively controlled on the basis of fully utilizing the advantages of the high specific capacity of lithium metal itself, so as to improve the performance of the secondary battery. The prepared secondary battery not only maintains a high energy density, but also has good stability and safety, while achieving an improvement in coulombic efficiency.
[0052] According to an embodiment of the present disclosure, the thickness of the negative electrode material is 10-100 μm, for example, the thickness can be 10 μm, 30 μm, 50 μm, 70 μm, 100 μm, etc. The surface density of the negative electrode material is 0.534-5.34 mg / cm², for example, it can be 0.534 mg / cm², 1.0 mg / cm², 2.0 mg / cm², 3.0 mg / cm², 4.0 mg / cm², 5.34 mg / cm², etc. The material of the positive electrode is selected from any one of lithium nickel cobalt manganese oxide and lithium iron phosphate; the electrolyte is selected from any one of trifluoromethylsulfonyl imide lithium electrolyte and bisfluorosulfonyl imide lithium electrolyte; the diaphragm is selected from any one of polyacrylic acid diaphragm, polyethylene diaphragm, and polysulfone diaphragm.
[0053] According to the embodiments of the present disclosure, the negative electrode material is processed by a rolling process, and the negative electrode material can be rolled into sheets with different thicknesses and surface densities. Furthermore, by adjusting the thickness and surface density of the negative electrode material, matching it with the corresponding positive electrode material, electrolyte and separator, a secondary battery suitable for a variety of application scenarios is constructed, such as electric vehicles, portable electronic devices, energy storage systems, etc.
[0054] According to an embodiment of the present disclosure, the negative electrode mass specific capacity of the secondary battery is 2000 mAh g -1 ~3100 mAh g -1 , for example, it can be 2000 mAh g -1 , 2300 mAh g -1 , 2500 mAh g -1 , 2700 mAh g -1 、3000 mAh g -1 、3100 mAh g -1 wait.
[0055] According to the embodiment of the present disclosure, a half-cell is prepared with a negative electrode material as the negative electrode and lithium metal as the counter electrode, and the voltage of the half-cell is charged to a cut-off voltage (such as 0.5V) to ensure that the capacity in the negative electrode is fully released. Combined with the mass data of the negative electrode, the mass specific capacity of the negative electrode material is calculated. The present disclosure increases the mass fraction of lithium metal in the negative electrode material to ensure that the negative electrode material has a high lithium metal utilization rate, so that the mass specific capacity of the negative electrode material in the secondary battery can reach 2000 mAhg -1 above.
[0056] In order to make the purpose, technical scheme and advantages of the present disclosure clearer, the present disclosure is further described in detail below in conjunction with specific examples and drawings. Specific techniques or conditions not specified in the examples are all conventional methods, which can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. It should be noted that the methods provided in the present disclosure are all conventional methods unless otherwise specified, and the reactants and reagents can be obtained from public commercial channels unless otherwise specified.
[0057] Embodiment 1:
[0058] This embodiment 1 provides a negative electrode material.
[0059] In an argon-protected glove box, weigh 2.0g (0.288mol) of lithium metal (Li) and the component metals used to form the metal alloy: 88.3mg (0.82mmol) of silver, 19.9mg (0.82mmol) of magnesium, 92.0mg (0.82mmol) of cadmium, and 22.1mg (0.82mmol) of aluminum. Heat the lithium metal at 300°C to a molten state, and gradually add the above-mentioned component metals while the lithium metal is molten and maintained at a high-speed stirring of 300 r / min. Continue to raise the temperature to 1000°C and maintain high-speed stirring for 20 minutes to obtain a molten alloy mixture. The molar ratio of lithium metal to metal alloy is 89:1, and the mass fraction of lithium metal is 90%;
[0060] The molten alloy mixture was naturally cooled to 25° C. in a glove box, and then rolled into an alloy sheet with a thickness of 10 μm to obtain the negative electrode material F1.
[0061] The negative electrode material in Example 1 was analyzed by transmission electron microscopy. Figure 1 It is a high-resolution transmission electron microscope image of the negative electrode material in Example 1 of the present disclosure and the corresponding energy dispersion X-ray spectrum surface distribution diagram.
[0062] like Figure 1As shown, the left picture is a high-resolution transmission electron microscope (TEM) picture of the negative electrode material at a scale of 20nm, and the right picture is an energy dispersive X-ray spectrum distribution (EDX mapping) picture of the negative electrode material at a scale of 20nm. It can be observed that silver (Ag), magnesium (Mg), cadmium (Cd), and aluminum (Al) are evenly distributed in the negative electrode material, and various metal elements are fully mixed without phase separation or element segregation, indicating that the negative electrode material has good uniformity and stability.
[0063] The negative electrode material in Example 1 was used to assemble a symmetrical battery. The counter electrode and working electrode of the symmetrical battery were both the negative electrode material F1 in Example 1, the electrolyte was a 1 mol / L lithium bis(fluorosulfonyl)imide (LiFSI) solution (the solvent included ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and the volume ratio of DME to TTE was 1.2:3), and the diaphragm was a polypropylene diaphragm from Celgard in the United States. The assembly process of the symmetrical battery was carried out in a Chinese Mi Cairo glove box to ensure that the ratio of oxygen and water in the glove box was less than 0.01 ppm, and the symmetrical battery D1 was assembled.
[0064] The assembled symmetrical battery was subjected to charge and discharge cycle tests. Figure 2 The voltage-specific capacity curve of the negative electrode material in Example 1 of the present disclosure during the charge and discharge process.
[0065] like Figure 2 As shown in the figure, the charge-discharge platform of the negative electrode material is low, around ±20mV, and has good voltage stability. At the same time, the negative electrode material exhibits a high mass specific capacity of about 3099 mAh g -1 .
[0066] The diffusion coefficient of lithium metal in the negative electrode material was tested using the chronoamperometric titration method (GITT). Figure 3 Graph showing the diffusion coefficient of lithium ions in the negative electrode material in Example 1 of the present disclosure.
[0067] like Figure 3 As shown, the assembled symmetrical battery D1 was tested using the chronoamperometric titration method (GITT). The test results showed that the diffusion coefficient of lithium ions in the negative electrode material can reach 10 -7 ~10 -5 cm 2 s -1 , indicating that the diffusion kinetics of lithium metal in the negative electrode material is significantly accelerated.
[0068] Comparative Example 1
[0069] This comparative example 1 provides a negative electrode material of pure lithium metal.
[0070] The negative electrode materials and copper foil in Example 1 and Comparative Example 1 were respectively used to assemble half-cells. The negative electrode materials in Example 1 and Comparative Example 1 were respectively used as the negative electrode of the half-cell, the copper foil was used as the counter electrode of the half-cell, the electrolyte was a 1 mol / L lithium bis(fluorosulfonyl)imide (LiFSI) solution (the solvent included ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and the volume ratio of DME to TTE was 1.2:3), and the diaphragm was a Celgard polypropylene diaphragm from the United States. The half-cell assembly process was carried out in a Chinese Micailona glove box, and the ratio of oxygen and water in the glove box was ensured to be less than 0.01 ppm, and a half-cell B1 with the negative electrode material in Example 1 as the negative electrode and the copper foil as the counter electrode and a half-cell B2 with the negative electrode material in Comparative Example 1 as the negative electrode and the copper foil as the counter electrode were assembled.
[0071] The two assembled half cells were tested for Coulombic efficiency. Figure 4 This is a comparison chart of the coulombic efficiency of a half-cell assembled with the negative electrode material and copper metal foil in Example 1 of the present disclosure and a half-cell assembled with the negative electrode material and copper metal foil in Comparative Example 1.
[0072] like Figure 4 As shown, at 2 mA cm -2 At a surface current density of , the half-cell assembled with the negative electrode material and copper metal foil in Example 1 of the present disclosure can stably cycle for more than 400 cycles, with an average coulombic efficiency of about 99.5%. Compared with the half-cell assembled with pure lithium metal and copper metal foil in Comparative Example 1, it has higher coulombic efficiency and better cycle stability, proving that the reversibility of lithium metal during the cycle is good.
[0073] The negative electrode materials in Example 1 and Comparative Example 1 were used as negative electrodes, respectively, the commercially available high nickel material NCM811 was used as positive electrode, the electrolyte was 1 mol / L lithium bis(fluorosulfonyl)imide (LiFSI) solution (the solvent included ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), the volume ratio was 1.2:3), and the diaphragm was American Celgard polypropylene diaphragm. The assembly process was carried out in a Chinese Micailona glove box to ensure that the ratio of oxygen and water in the glove box was less than 0.01ppm, and a button-type secondary battery E1 with the negative electrode material in Example 1 as the negative electrode and NCM811 as the positive electrode and a button-type secondary battery E2 with the negative electrode material in Comparative Example 1 as the negative electrode and NCM811 as the positive electrode were assembled.
[0074] Conduct electrochemical performance tests on secondary batteries E1 and E2. Battery testing uses China Xinwei battery testing system or Blue Power battery testing system. Figure 5The graph is a comparison of the cycle performances of secondary batteries assembled using the negative electrode materials in Example 1 and Comparative Example 1.
[0075] like Figure 5 As shown, the secondary battery E1 has excellent performance in the battery rate test: it cycles more than 500 times under the conditions of 0.5C charging and 1C discharging, and the capacity retention rate is about 100% after 100 cycles, and the capacity retention rate is more than 90% after 500 cycles. Compared with the secondary battery E2 (the capacity drops sharply after 100 cycles), the performance is significantly improved.
[0076] Example 2
[0077] This embodiment 2 provides a negative electrode material.
[0078] Compared with Example 1, the difference is that the component metals used to form the metal alloy in this embodiment are: 98.0 mg (0.91 mmol) silver, 22.1 mg (0.91 mmol) magnesium, 102.1 mg (0.91 mmol) cadmium, and the remaining preparation steps are consistent with Example 1.
[0079] Example 3
[0080] This embodiment 3 provides a negative electrode material.
[0081] Compared with Example 1, the difference is that the component metals used to form the metal alloy in this embodiment are: 150.6 mg (1.40 mmol) silver, 33.9 mg (1.40 mmol) magnesium, 37.7 mg (1.40 mmol) aluminum, and the remaining preparation steps are consistent with Example 1.
[0082] Example 4
[0083] This embodiment 4 provides a negative electrode material.
[0084] Compared with Example 1, the difference is that the component metals used to form the metal alloy in this example are: 33.0 mg (1.36 mmol) magnesium, 152.6 mg (1.36 mmol) cadmium, 36.6 mg (1.36 mmol) aluminum, and the remaining preparation steps are consistent with Example 1.
[0085] Example 5
[0086] This embodiment 5 provides a negative electrode material.
[0087] Compared with Example 1, the difference is that the component metals used to form the metal alloy in this example are: 96.9 mg (0.90 mmol) silver, 101.0 mg (0.90 mmol) cadmium, 24.2 mg (0.90 mmol) aluminum, and the remaining preparation steps are consistent with Example 1.
[0088] The negative electrode materials in Examples 2 to 5 were used to assemble half-cells with lithium metal. The negative electrode materials in Examples 2 to 5 were used as the negative electrode of the half-cell, lithium metal was used as the counter electrode of the half-cell, the electrolyte was a 1 mol / L lithium bis(fluorosulfonyl)imide (LiFSI) solution (the solvent included ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and the volume ratio of DME to TTE was 1.2:3), and the diaphragm was a Celgard polypropylene diaphragm from the United States. The half-cell assembly process was carried out in a Chinese Micailona glove box, in which the ratio of oxygen and water was ensured to be less than 0.01 ppm, and four half-cells were assembled with the negative electrode materials in Examples 2 to 5 as the negative electrode and lithium metal as the counter electrode.
[0089] The mass specific capacity of the negative electrode materials in Examples 1 to 5 was tested. The half-cell voltage obtained by assembling the negative electrode materials in Examples 1 to 5 was charged to a cut-off voltage (e.g., 0.5 V) so that the capacity in the negative electrode was fully released, and the mass specific capacity of each negative electrode material was calculated based on the mass value of the negative electrode. Figure 6 4 is a comparison chart of the mass specific capacity of the negative electrode materials in Examples 1 to 5 of the present disclosure.
[0090] like Figure 6 As shown, from left to right, they are the negative electrode material (Li-Ag Mg Cd Al combination) in Example 1, the negative electrode material (Li-Ag Mg Cd combination) in Example 2, the negative electrode material (Li-Ag Mg Al combination) in Example 3, the negative electrode material (Li-Mg Cd Al combination) in Example 4, and the negative electrode material (Li-Ag Cd Al combination) in Example 5, and the corresponding average mass specific capacity is 2921 mAh g -1 、2117 mAh g -1 、2648 mAh g -1 , 2620 mAh g -1 and 2489 mAh g -1 , indicating that the negative electrode material prepared by the combination of Li-Ag Mg Cd Al releases the highest mass specific capacity.
[0091] Example 6
[0092] This embodiment 6 provides a negative electrode material.
[0093] Compared with Example 1, the difference is that the mass fraction of lithium in this embodiment is 80%, and the other preparation steps are consistent with Example 1.
[0094] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.
Claims
1. A negative electrode material, comprising: Lithium metal and metal alloys, wherein The metal alloy includes a metal that forms a solid solution with the lithium metal; The mass fraction of the lithium metal includes 60% to 90%; The valence electron concentration of the metal alloy is less than 6.87; The utilization rate of lithium metal in the negative electrode material is higher than 35%.
2. The negative electrode material according to claim 1, characterized in that The metal capable of forming a solid solution with lithium metal is selected from at least two of indium, magnesium, silver, cadmium, zinc and aluminum, preferably at least four of indium, magnesium, silver, cadmium, zinc and aluminum.
3. The negative electrode material according to claim 2, characterized in that The molar ratio of the lithium metal to the metal alloy is 55-90:
1.
4. A method for preparing the negative electrode material according to any one of claims 1 to 3, comprising: Under the protection of an inert gas, the lithium metal and the metal alloy are melted and mixed to form a molten alloy mixture; The negative electrode material is obtained by cooling the molten alloy mixture.
5. The preparation method according to claim 4, characterized in that: The melt mixing time is 10 to 60 min; The temperature of the melt mixing is 180-1000°C.
6. The preparation method according to claim 4, characterized in that: The cooling includes: natural cooling or liquid nitrogen cooling.
7. A secondary battery comprising a negative electrode, a positive electrode, an electrolyte and a separator, wherein: The negative electrode comprises the negative electrode material according to any one of claims 1 to 6, The separator is located between the negative electrode and the positive electrode, and the electrolyte is filled in the gaps between the separator and the positive electrode and the negative electrode.
8. The secondary battery according to claim 7, characterized in that: The thickness of the negative electrode material is 10-100 μm, and the surface density of the negative electrode material is 0.534-5.34 mg / cm².
9. The secondary battery according to claim 7, characterized in that: The material of the positive electrode is selected from any one of lithium nickel cobalt manganese oxide and lithium iron phosphate; The electrolyte is selected from any one of trifluoromethylsulfonyl imide lithium electrolyte and bis(fluorosulfonyl imide) lithium electrolyte; The diaphragm is selected from any one of a polyacrylic acid diaphragm, a polyethylene diaphragm, and a polysulfone diaphragm.
10. The secondary battery according to any one of claims 7 to 9, characterized in that: The negative electrode mass specific capacity of the secondary battery is 2000 mAh g -1 ~3100 mAh g -1 .
Citation Information
Patent Citations
Multi-element lithium-magnesium alloy negative electrode material for high-cycle-stability secondary battery and adaptive electrolyte thereof
CN110797524A
Electrode materials in the form of lithium-based alloy and methods for manufacturing same
CN110998920A
Metal lithium alloy electrode material, preparation method thereof and metal lithium secondary battery
CN111048744A
Composite lithium metal negative electrode material and preparation method thereof
CN111816836A
High-entropy lithium alloy negative electrode and preparation method thereof
CN115986064A